Individual differences in the development of scientific thinking in kindergarten. (August 2018) - van der Graaf, Joep; Segers, Eliane; Verhoeven, Ludo
Abstract: The present study examined the development of and individual variation in scientific thinking in kindergarten. We measured experimentation, evidence evaluation, and domain knowledge at two times in kindergarten (T1 and T2) in a sample of 100 five to six-year-olds. To explain individual differences, executive functions and linguistic abilities (grammar and vocabulary) were assessed one year earlier (T0). Executive functions and grammatical abilities predicted scientific thinking and its development from T1 to T2. Kindergartners grew in scientific thinking with evidence evaluation predicting the growth in domain knowledge. These results showed that evidence evaluation is important to acquire domain knowledge. Executive functions appeared to be a predictor of development in general. It is recommended that in early science education language should be taught in concurrence with scientific thinking in order to structure children's thoughts and guide their actions, as the present study showed that grammar predicted proficiency in experimentation and evidence evaluation. Highlights: There is a significant growth in scientific thinking at kindergarten age. Acquisition of domain-specific knowledge was predicted by the ability to evaluate evidence. Scientific thinking and its development relies on executive functions and linguistic abilities. Teaching of science, both skills and knowledge, seems feasible in kindergarten.